Market Reaction to Tax Amnesty Information: Survey on Indonesian Public Listed Companies - Arie Pratama (AFEBI Accounting Review, 2021)
This article described the Indonesian market reaction on the announcement of tax amnesty related information in the financial statements. Statement of Financial Accounting Standards (SFAS) No. 70 required companies to recognized and measured the tax amnesty's assets. Tax amnesty's asset was selected as information to be analyzed. The total of 141 observations from the year 2016 – 2017 financial statements were selected as a sample. To measure market reaction, three proxies were used: value relevance, cumulative abnormal return, and trading volume activity. Data analyzed using linear regressions.  This article showed that the market reacted to tax amnesty information, although the level of reaction was low. This article also showed that in general, market reaction toward tax amnesty was positive. These results also implied that the SFAS 70's accounting requirement improved the quality of financial statements.